A new model for nulling and moding in radio pulsars. Issue Volume 16:Issue S363(2020) (June 2020) - Dyks, Jaroslaw
Abstract: Single pulse behaviour of radio pulsars is usually interpreted in terms of the E × B drift of a radio beam. It is shown that antisymmetric arrangement of the radio-bright zones can produce several types of observed single pulse phenomena: the half-cycle jump in subpulse modulation phase, left-right-middle subpulse sequence and switching between the core-dominated and cone-dominated pulsation modes. The geometry can also produce nulling, both sporadic and intermodal. The model implies that the radio-quiet intervals that separate the main pulse and interpulse in PSR B0826−34 correspond to azimuthal breaks in the radio beam, instead of breaks in colatitude.